Taxonomic revision of the genus Calendula (Asteraceae) in the Canary Islands - Simão, Inês; Reyes-Betancort, J. Alfredo; Talhinhas, Pedro; Morais-Cecílio, Leonor; Silveira, Paulo (Phytotaxa, 2024)
A taxonomic revision of the genus Calendula (Asteraceae – Calenduleae) for the Canary Islands is presented. An extensive morphometric analysis was conducted on specimens held in several herbaria and collected by the team, as well as chromosome counts and genome size estimates. Four species of Calendula were recognized in the islands: C. arvensis, C. officinalis, C. ricardoi, and C. sventenii, the latter two being new taxa, described for the first time in this work. Descriptions, an identification key, distribution areas, ecology and conservation assessments for each taxon are presented, as well as discussions of the possible origins of the taxa in the territory.